Role of temperature on linearity and analog/RF performance merits of a negative capacitance FinFET - Jaisawal, Rajeewa Kumar; Rathore, Sunil; Gandhi, Navneet; Kondekar, Pravin N; Bagga, Navjeet (Semiconductor science and technology, 2022)
Temperature plays a decisive role in semiconductor device performance and reliability analysis. The effect is more severe in a negative capacitance (NC) transistor, as the temperature modulates the ferroelectric polarization, implicitly included by the Landau coefficients ( α, β, γ ) in Technology Computer Aided Design (TCAD) simulations. In this paper, through TCAD simulations, the role of varying ambient temperature is investigated in the linearity and analog/radio-frequency (RF) merits of NC-FinFET. The varying temperature modulates the carrier mobility, the semiconductor bandgap, and the Landau parameter ( α ). We analyzed the analog/RF and linearity metrics, such as total gate capacitance ( C gg ), transconductance ( g m ), unity gain cut-off frequency ( f T ), the transconductance-frequency product, gain-bandwidth product, higher-order transconductance ( g m2 and g m3 ), voltage intercept points, third-order power intercept and intermodulation points, and 1 dB CP using well-calibrated TCAD models. Our analysis reveals that these parameters are strongly dependent on temperature and the NC span (defined by using S-curve) shrinks with the rise in temperature. Finally, a source follower and three-stage ring oscillator are designed to test the frequency compatibility of the AC simulation for varying temperatures.